Pengaruh Jenis Kemasan Terhadap Sifat Organoleptik Tape Singkong - Nurul Hidayah; Basirun Basirun (Nutriology : Jurnal Pangan,Gizi,Kesehatan, 2021)
Abstrak bahasa Inggris: Cassava tape is originally local food from Indonesia. This product is fermented resulting different sensory properties. The application of various packaging to wrap cassava when making tape; however, there is no research, which compares the effect of several packaging to organoleptic properties of cassava tape. This research aims to figure out the effect of different packaging to organoleptic characteristic of cassava tape. The result was designed using completely randomized design (RAL) and analysed by variant analysis (Anova). Duncan Multiple Range Test (DMRT )was used to test significant results. According to the analysis, there was a significant difference in different packaging used to the organoleptic perception of cassava tape, especially in flavor, taste, sweetness level, and texture. There was a strong alcoholic flavor, a very liked taste, high sweetness level, and soft texture. The use of plastic jar tends to trigger no alcoholic flavor, unliked taste, no sweetness, and hard texture. When using a plastic bag it had almost similar flavor, color and taste to the tape wrapped with banana leave; however, it has less sweetness and less soft texture. In conclusion, based on the result it is recommended to pack the cassava with banana leave to obtain greater sensory properties according to what consumers’ desire.